Vitamin E levels in patients with controlled and uncontrolled type 2 diabetes mellitus - Iranparvar Alamdari, Manouchehr; Habibzadeh, Shahram; Shahbazzadegan, Bita; Mazani, Mohammad; Bigdeli, Amir; Shahbazi, Ali (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes type 2 associates with increased oxidative stress and reduced antioxidant. Vitamin E supplementation reduces oxidative stress in diabetic patients. We intended to measure the level of this vitamin in these patients to assess its relationship in control of patients’ diabetes by designing present study. Methods: This is a descriptive and cross-sectional study and carried out on 186 patients with diabetes type 2 diagnosis. The levels of HbA1C (measured by HPLC method), TG, cholesterol, HDL, LDL and Cr were measured, and given to that the level of HbA1C lower than 7 (controlled group) and or more than 7 (uncontrolled group), patients were divided in two groups. Were designed a check list involved questions such as age and information of each patient associated with measured vitamin E level were entered into the check list and after that were analyzed data. Results: In the existing study 186 diabetic patients were examined. From within examined patients, 129 (69.3%) were women and the rest were men and average patients age were 53.33±11.2. In this study was observed there was no direct correlation between the level of cholesterol (p=0.284), LDL (p=0.538( and HDL (p=0.362) with controlled DM II in patients while in uncontrolled diabetic the triglyceride levels was more than those with controlled blood sugar significantly (p=0.046(. The average vitamin E level in patients was 1488.6±692.2 nmol/l its lowest level 114.4 nmol/l and the highest level was 6235 nmol/l. Conclusions: The results of this study show that the vitamin E levels no significant difference between control and non-control diabetic patients.